The Utilization of Learning Media: Comparison of Pop-Up Book and Flip Book Media in Improving Elementary School Students' Reading Comprehension Skills - Dewi Fitriani (Bulletin of Science Education, 2024)
This study was conducted in class VI SDN Pasirhalang 2, Sukabumi Regency with the aim of knowing the differences between pop-up book and flip book media on elementary school students' reading comprehension skills. This study is an experimental research with a one-shot case study design. In this design, the researcher only conducted one treatment which was estimated to have an effect. This design was used to examine the process and achievement of student learning outcomes during the learning given to class A using pop-up book media while class B used flip book media. In this study, there were two groups, namely randomly selected. This research design used one class A and one class B. After being given media to one of the sample groups (experiment), it was continued with the provision of the two sample groups (control) used. The data obtained were student learning outcome data collected from two classes, namely 30 class VI SDN Pasirhalang 2 (class B) and 30 class IV SDN Pasirhalang 2 (class A) with a total of 60 students. The average value in the experimental class is 66.5 with a minimum value of 40 and a maximum value of 90. While the average value in the control class is 61.59 with a minimum value of 40 and a maximum value of 87.5. Based on the results of data processing using the hypothesis test (F one way anova test) obtained a significance value (Asymp sig (2-tailed) 0.03 <0.05, it can be stated that Ho is rejected and H₁ is accepted. It can be concluded that there is a significant difference when using pop up book and flip book media.